P-B04 Restarting bariatric surgery after the Covid-19 pandemic: a template for safe practice. (16th December 2021) - Michel, Martin; Fifer, Helen; Moran, Emily; Saab, Ala; Hammett, Felix; Kronberga, Madara; Bonner, Clare; Saha, Arin; Salih, Tamir; Peter, Mark
Abstract: Background: Bariatric surgery virtually ceased with the advent of the Covid-19 pandemic and has been amongst the last sector of operative practice to restart. There have been understandable concerns about restarting bariatric surgery including the risks to patients of contracting Covid infection in the peri-operative period, potential de-skilling of surgeons and theatre teams and the appropriateness of directing scarce and limited resources to bariatric surgery when every surgical specialty is experiencing rapidly rising waiting times and ever lengthening waiting lists. This study describes the restart programme at our NHS bariatric unit and offers a template for safe commencement of complex benign surgeries in the current era. Methods: In the months after the pandemic started, our Bariatric MDT reviewed every case on the waiting list and contacted each patient to explain the current waiting times and the importance of not gaining weight to be eligible for surgery when surgical practice resumed. Group education and Support Group sessions were moved from face-to-face appointments to online classrooms and regular input was sought from specialist dieticians, nurses and psychologists. The expected waiting times for patients was pro-actively submitted to the Executive Board of the Trust with details about >104-week waiting patients being clearly articulated. Once approval was given to restart bariatric surgery, every patient was assessed and prioritised in terms of waiting time and clinical need. A bariatric theatre team was brought together and engaged in pre-operative training and a local refresher course on equipment and the planned surgeries. There was engagement with industry to provide on-the-ground support for the first lists to ensure proper and safe use of energy and stapling devices. Each list had two consultant surgeons assigned to it and just two cases per day were planned and patients were managed on an entirely green pathway within the NHS hospital . Results: The bariatric restart programme commenced in May 2021; between May 2021 and August 2021, there have been 27 operations carried out (25 Roux-en-Y gastric bypass, 2 sleeve gastrectomy) and two cancellations on the day (both due to patient choice). Each operating list finished between two and three hours before the planned finish time. Formal debrief sessions after each list identified no problems with the operations of the equipment and none of the patients had any post-operative complications. Length of stay was between 1 to 2 days for the entire cohort. Since the restart programme commenced, the requirement for dual consultant operating has ceased and the last 5 cases have been entirely training cases for the operating registrar, again without complication. Each list is now planned to increase to pre-pandemic levels of activity with four cases per list. Conclusions: Restarting complex benign surgical practice is complicated and requires engagement with management, theatre and nursing colleagues to ensure that cases are not 'left behind'. It is important to reduce the risk of complications and of peri-operative covid-19 infection in bariatric patients and development of a pathway that all members of the theatre team have input in to meant that there were few problems or issues with either the planning of the lists or the running of the lists. Such an approach could be considered for restarting any high volume, complex benign surgical practice.